The influence of “Fight Dengue Campaign” message framing strategy toward prevention behaviour among resident at Sungai Petani / Nur Rahimah Zubaidi and Siti Nur Juliana Johari - Zubaidi, Nur Rahimah (2018)
This chapter provides an overview of this study, which consists of eight main sections. Beginning with the background of study, this chapter identifies the issues ascertain the research problem, research problem and the objective of this research endeavor. It also highlights the significance, scope of study, provides the definition of terms and concludes with a discussion on the remaining chapters.